The hydroid and medusa of Corymorpha januarii in temperate waters from the Southwestern Atlantic Ocean - Genzano, Gabriel Nestor (2009)
During several surveys conducted in shallow, temperate waters of northern Patagonia, we found hydroids belonging to the family Corymorphidae. Additionally, sorting more than 2700 plankton samples yielded five specimens of a corymorphid medusa. Both stages belong to Corymorpha januarii Steenstrup, 1854, a hydrozoan rarely reported in the literature. This finding extends southwards its geographic distribution and represents the first Subantarctic record, as well as the first finding of the medusa stage in nature, confirming its endemism in the tropical and temperate waters of the Southwestern Atlantic.